Urgensi Kebutuhan Penerjemah Lisan Bahasa Daerah di Pengadilan: en_US - Nugroho, Agus Digdo Nugroho; Johanes, Johanes (Jurnal Penerjemahan, 2024)
The use of local languages in most courts in Indonesia still exists. Local languages are used as the language of daily communication even when conducting trials and accessing services at the court office. The fact that local languages are still used forces the court as a justice service provider to adjust its service communication by organizing local language translators and interpreters in the court. The conditions that occur are that interpreters and local language oral translators in court are appointed without regard to work professionalism, competence, budget support, or other technical matters. In this journal article, the author will present a description of the forms of local languages in several courts and the conditions of oral translators and interpreters in court. The method used is a qualitative method with data available in the electronic media of the court's website regarding the decision to procure local language interpreters and translators. The findings in this translation journal research are the fact that in each court throughout Indonesia, the use of local languages in communicating both in court and when accessing court services is still recognized. This condition requires courts to adjust communication in the use of local languages by learning the local language or providing interpreters as well as translators to support the implementation of the duties and functions of the court.